anonymous
  • anonymous
solve the first order differential equation: y-x(dy/dx)=(dy/dx)y^2e^y
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Rearrange the equation to put it into a standard form,\[y-(x^2+y^2e^y)\frac{dy}{dx}=0\]which is in the form, \[M(x,y)+N(x,y)\frac{dy}{dx}=0\]We check to see if it's exact. We need to ensure,\[\frac{\partial M}{\partial y}=\frac{\partial N}{\partial x} \rightarrow 1=1\]which is true. Now,
anonymous
  • anonymous
the potential function,\[\Psi(x,y)\]has that\[\frac{\partial \Psi}{\partial x}=M=y\]and\[\frac{\partial N}{\partial x}=N=-x^2-y^2e^y\]
anonymous
  • anonymous
Integrate the first partial:\[\Psi(x,y)=xy+c(y)\]and then take the partial derivative of this result with respect to y,\[\frac{\partial \Psi}{\partial y}=x+c'(y)\]so that we can identify it with \[\frac{\partial \Psi}{\partial y}=-x^2-y^2e^y\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

nowhereman
  • nowhereman
Above you were saying \[\frac{∂N}{∂x} = 1\] while indeed it is \[-2x\]
anonymous
  • anonymous
(note a mistake above dN/dx should be dPsi/dy)
nowhereman
  • nowhereman
I mean where you say "We check to see if it's exact."
anonymous
  • anonymous
Oh - thanks nowhereman - typo with x^2...it should just be x
nowhereman
  • nowhereman
right :-)
anonymous
  • anonymous
great - now the whole thing's polluted.
anonymous
  • anonymous
\[\frac{\partial \Psi}{\partial y}=-(x+ye^y)=x+c'(y)\]
anonymous
  • anonymous
so that\[c'(y)=-2x-ye^y \rightarrow c(y)=-2xy-e^y(y^2-2y+2)\]where the last integral is doable using a few integration by parts. Sub. this back in for our solution Psi to give,\[\Psi(x,y)=xy-2xy-e^y(y^2-2y+2)\]\[=-xy-e^y(y^2-2y+2)+c=K\]
anonymous
  • anonymous
where c is the constant of integration, and K is a constant due to the fact that this function Psi satisfies\[\frac{d \Psi(x,y)}{dx}=\frac{\partial \Psi}{\partial x}\frac{dx}{dx}+\frac{\partial \Psi}{\partial y}\frac{dy}{dx}=\Psi_{x}+\Psi_y \frac{dy}{dx}=0\]which is the form of the equation we had to solve in the beginning.
anonymous
  • anonymous
Are you seeing any mistakes, nowhereman?
anonymous
  • anonymous
So \[\Psi(x,y)=-xy-e^y(y^2-2y+2)=c\]for c, some constant.

Looking for something else?

Not the answer you are looking for? Search for more explanations.